Tribological coatings for complex mechanical elements produced by supersonic cluster beam deposition of metal dichalcogenide nanoparticles. (29th May 2015) - Piazzoni, C; Buttery, M; Hampson, M R; Roberts, E W; Ducati, C; Lenardi, C; Cavaliere, F; Piseri, P; Milani, P
Abstract: Fullerene-like MoS2 and WS2 nanoparticles can be used as building blocks for the fabrication of fluid and solid lubricants. Metal dichalcogenide films have a very low friction coefficient in vacuum, therefore they have mostly been used as solid lubricants in space and vacuum applications. Unfortunately, their use is significantly hampered by the fact that in the presence of humidity, oxygen and moisture, the low-friction properties of these materials rapidly degrade due to oxidation. The use of closed-cage MoS2 and WS2 nanoparticles may eliminate this problem, although the fabrication of lubricant thin films starting from dichalcogenide nanoparticles is, to date, a difficult task. Here we demonstrate the use of supersonic cluster beam deposition for the coating of complex mechanical elements (angular contact ball bearings) with nanostructured MoS2 and WS2 thin films. We report structural and tribological characterization of the coatings in view of the optimization of tribological performances for aerospace applications.